2018
DOI: 10.2147/ott.s156421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on efficacy of PD-1/PD-L1 inhibitors in non-small cell lung cancer patients: a meta-analysis

Abstract: BackgroundSmoking status is associated with the efficacy of non-small cell lung cancer (NSCLC) treatment. Latest clinical trials have depicted the difference in the effectiveness of programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors in smokers and nonsmokers. However, the lack of statistical power in these trials prevented a final conclusion. The authors postulated that the efficacy of PD-1/PD-L1 inhibitors correlated with smoking status.Materials and methodsClinical trials evaluating P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
5
38
0
Order By: Relevance
“…Then, we drew a conclusion that regardless of smoking or not, patients in the experimental arms always benefit, which is consistent with the analysis of Lee et al [19]. It seemed that the conclusions drawn by Abdel-Rahman [17] and Li et al [18] could be reversed. Given the higher heterogeneity, we observed these 15 studies and hypothesized that differences in therapeutic regimens (anti-PD-1/PD-L1 monotherapy/ combined chemotherapy) of the experimental arms might be the underlying cause of heterogeneity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Then, we drew a conclusion that regardless of smoking or not, patients in the experimental arms always benefit, which is consistent with the analysis of Lee et al [19]. It seemed that the conclusions drawn by Abdel-Rahman [17] and Li et al [18] could be reversed. Given the higher heterogeneity, we observed these 15 studies and hypothesized that differences in therapeutic regimens (anti-PD-1/PD-L1 monotherapy/ combined chemotherapy) of the experimental arms might be the underlying cause of heterogeneity.…”
Section: Discussionsupporting
confidence: 78%
“…Although previous meta-analyses have attempted to clarify the relationship between smoking and the efficacy of ICIs [17,18], due to the limitations of the number of studies, the types of carcinomas and lack of subgroup analysis, the results remained to be confirmed. In this meta-analysis, we included a large amount of high-quality trials without any restriction on carcinoma category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted, that smoking status differentially modulates the response of patients to CPI treatment. In a phase III randomized control trial with 1981 NSCLC patients, PD-1 inhibitors worked more efficaciously in patients with a smoking history while nonsmoking patients showed no survival benefit [ 121 ]. A similar meta-analysis in NSCLC, urothelial cancer and HNSCC showed that smokers benefited from anti PD-1/PD-L1 mono or combination therapy while nonsmokers benefitted from a combination of chemo- and immunotherapy [ 122 ].…”
Section: Influence Of Lifestyle On Outcome Of Cpimentioning
confidence: 99%
“…Here, we retrospectively examined the relationship between smoking and efficacy of PD-(L)1 inhibitors among 315 patients with PD-L1 TPS ≥50%. Based upon retrospective studies in unselected patient populations, 9 , 14 we had originally hypothesized that never/light smokers would have limited clinical benefit from PD-(L)1 inhibition even in the setting of high PD-L1 expression. Instead, we observed fewer differences than initially anticipated.…”
Section: Discussionmentioning
confidence: 99%